(untitled) (Journal of Information Technologies in Education (ITE), 2013)
This paper are presented the principles of construction of conceptual model of the information system «Scientific researches» for automation of management of scientific researches in NAPS of Ukraine. Research results are described in relation to forming of the fields and automation of treatment of documents in the integrated environment of MS Sharepoint, which was conducted within the limits of implementation of R&D «Scientifically methodical providing of the information system of planning of scientific researches in Academy of pedagogical sciences of Ukraine on the base of network the Internet»